2020
DOI: 10.1038/s41598-020-71283-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors and early biomarkers of response in multiple sclerosis patients treated with natalizumab

Abstract: there are an increasing number of treatments available for multiple sclerosis (MS). the early identification of optimal responders to individual treatments is important to achieve individualized therapy. With this aim, we performed a multicenter retrospective longitudinal study including 186 MS patients treated with natalizumab who were followed for 2 years. We analyzed the following variables at recruitment: sex, current age, age at disease onset, disease duration, EDSS, number of T2 and Gd + lesions, IgG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In this study, as we can see, in Supplementary Figure S1 , that HHV-6A/B IgG titers were not statistically significantly different between SPMS patients and HC, while the p -value was even more significant when we compared RRMS patients and HC ( p = 0.0008) than when we compared the whole population of MS patients with the HC ( p = 0.003). This is a cross-sectional study and we have not analyzed the relation between the evolution of the HHV-6A/B IgG titers and the progression of the disease in each patient, as we have done in other longitudinal studies [ 3 , 59 ]. Finally, since a paper analyzing HHV-6A and HHV-6B in MS patients has been recently published using a novel multiplex serological assay, it would be very interesting for future studies to know if the observed negative correlation between IgG titers and MSSS in treated MS patients is due to one of these two viruses or not [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as we can see, in Supplementary Figure S1 , that HHV-6A/B IgG titers were not statistically significantly different between SPMS patients and HC, while the p -value was even more significant when we compared RRMS patients and HC ( p = 0.0008) than when we compared the whole population of MS patients with the HC ( p = 0.003). This is a cross-sectional study and we have not analyzed the relation between the evolution of the HHV-6A/B IgG titers and the progression of the disease in each patient, as we have done in other longitudinal studies [ 3 , 59 ]. Finally, since a paper analyzing HHV-6A and HHV-6B in MS patients has been recently published using a novel multiplex serological assay, it would be very interesting for future studies to know if the observed negative correlation between IgG titers and MSSS in treated MS patients is due to one of these two viruses or not [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the fact that women had slightly higher baseline inflammatory MRI activity. Other studies have shown that the risk of not achieving NEDA was associated with clinical and MRI measures of disease activity and progression (e.g., higher baseline EDSS score, number of relapses in the previous 12 months, number of CELs) [ 33 , 34 , 35 ]. Conversely, studies of the prognostic value of NEDA status over 2 years in predicting future disability progression up to 10 years have provided conflicting data, but this was related to the DMT used, with few patients maintaining NEDA over the long term in studies in which self‐injectable DMTs were used, while NEDA was enhanced in patients over the long term in studies utilizing more effective DMTs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent work, Dominguez-Mozo et al described that higher titer of IgG HHV-6 antibodies are related to the occurrence of disease relapses in patients with MS and that treatment with natalizumab drastically reduces both the relapse rate and IgG HHV-6 antibody titers. Based on these data, the authors highlight the potential role of these antibodies not only as predictive factors, but also as early biomarkers of drug response in patients with MS [ 70 ].…”
Section: Classification Of Biomarkersmentioning
confidence: 99%